Motivasi Kerja dan Strategi Meningkatkan Kemampuan ASN Pada DPMD Kabupaten Musi Banyuasin - Wandira, Firdanita; Liana, Wendy; Wadjdi, Farid (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2022)
The purpose of the survey is to: (a) identify factors that support employee motivation in DPMD office in Musi Banyuasin Regent; (b). To know and analyze the strate-gies implemented by the office to increase the motivation of employees for the implementation of planned programs. The methods used in this study are qualitative. Data collection techniques used are interviews, observations, and documentation. The research result is 1). The internal factors for improving employee performance in DPMD are a) strengths, (1) number of people, and (2). Improved payroll system. (3). Education, expertise and skills of employees you can trust. (Four). There are empowerment programs and their implementation. b) (1) The weakness of having many employees but not enough office space. (2). Inadequate facilities and infrastructure; (3). classical computer; (4). Far from family on average, less than optimal performance. b). The outside is an opportunity consisting of (a) (1). Career Development Opportunities; Advertising etc. (2). Compete for leadership ratings. (3). Opportunities for further education; (4). Opportunity to do the best you can for career advancement. b) Threats consisting of (1) at least those who participate; (2). Democratic leaders are scarce. (3). Duplication of work due to unclear main tasks. (Four). Restrictions on Procurement of Qualified Persons. 2). In her SO strategy, her strategy to motivate DPMD's employees is to leverage strengths, and professionally trained and trained people to seize opportunities.